Analisis Kinerja Keuangan Desa Bojonggede dari Tahun 2018 - 2022 - Febriano, Muhammad Rasya; Gurendrawati, Etty; Khairunnisa, Hera (LPPM Universitas Negeri Jakarta, 2024)
This research aims to determine and analyze the health and financial performance of the village government in Bojonggede for the 2018-2022 budget period. This research uses various financial ratios that are useful for measuring financial performance, namely the Degree of Decentralization Ratio, Financial Independence Ratio, Efficiency Ratio and Effectiveness Ratio, and this research adds income growth to Total Income. This research is a type of qualitative descriptive research using secondary data and interviews with the Head of Village Government in the form of a Village Government Revenue and Expenditure Budget Realization Report (APBDes) in Bojonggede for the 2018-2022 budget period. The Financial Performance of the Village Government in Bojonggede Regency based on the Degree of Decentralization Ratio has a low level of capability, the Financial Independence Ratio has a very low level of independence and has an instructive relationship, the Results of the Effectiveness Ratio have an effective level, while the results of the Efficiency Ratio have a less efficient level. For the Income Growth Ratio whose value fluctuates, either up or down.